Features of the use of digital Risk management tools in the capital market and the organized commodity market - Liudmyla Parii; Tetiana Makarenko; George Abuselidze; Anna Slobodianyk; Olga Mohylevska; Ihor Sidak (E3S Web of Conferences, 2023)
The article discusses the features of the introduction of digital risk management tools in the capital market and the organized commodity market. In the course of research, it has been proved that a detailed classification of exchange risks is necessary for their identification at the stage of developing an exchange agreement, planning the income of all participants in an organized commodity market: enterprises (clients of the trading platform), brokers and others. It is proved that the price of grain, determined not so much by the costs of the commodity producer, as by supply and demand and the political situation in the relevant market, is a key element determining the profitability of their economic activities. The current situation shows that the development of an organized commodity market for grain futures will reduce the number of futures transactions concluded by investors on foreign exchanges, thereby increasing the capitalization of domestic trading platforms operating in the capital market and organized commodity market and generally increase the competitiveness of the financial market. Since in a market economy there are frequent fluctuations in prices for goods and services, ex-change rates, interest rates, these facts are catalysts not only for pre-dicting future market conditions, but also for insuring their activities, which will allow hedging on another person, more often on a financial intermediary (speculator). The tools for risk management at the enterprise are highlighted, which can be used by commodity producers independently, while the tools for transfer and risk sharing assume the existence of an appropriate institutional environment and market infrastructure. It is noted that the use of risk management in working with grain futures can allow agricultural producers, processors, elevators to increase the profitability of their enterprises by insuring risks from adverse price changes (especially during a period of high market volatility) in an organized commodity market; to participate in the formation of a fair market price for grain; to plan and control the monetary results of activities more accurately; to ensure the reliability of calculations; to get the best credit opportunities in banks; to expand opportunities for buying and selling grain.
Keywords: 330